Las aventuras de Ulises en la vieja Irlanda (Minerva, 2019)
Beginning with the Middle Irish version of the Odyssey the present article traces references to Ulysses throughout Early Irish Literature. The study involves the question of the transmission of Classical sources. For this purpose, the evidence for some acquaintance with Greek in early Christian Ireland, as well as the readiness to adapt Classical legends to suit native conditions, is discussed below.